Pelatihan Manajemen Keuangan Syariah Untuk Mencegah Jeratan Pinjaman Online Ilegal - Ayu Isnaeni Savaroza; Ayu Mentari Mutmainnah; Leniwati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
Sharia Financial Management training is crucial for the community as a primary solution amidst the massive onslaught of destructive digital debt instruments on social media. This training aims to increase public understanding and awareness of the characteristics, modus operandi, and legal and social risks of illegal online loans, and equip the public with practical skills for developing adaptive, independent financial planning and management based on Sharia financial management. Data collection was conducted through three simple steps: testing participants' understanding with questionnaires at the beginning and end of the event, observing participants' abilities while practicing checking official online loans on the Financial Services Authority website, and engaging participants in casual conversations after the training to hear about changes in their money management practices. Finally, the data was analyzed by statistically calculating test score increases and summarizing the results of the casual conversations into comprehensive conclusions. The results of this activity can enrich the literature on community service and Islamic economics, demonstrating that solving the problem of illegal online loans is not only sufficient through legal regulations but also requires reconstructing a Sharia-based financial mindset at the household level.